2010
DOI: 10.1007/978-3-642-16958-8_21
|View full text |Cite
|
Sign up to set email alerts
|

Scalable and Robust Shepherding via Deformable Shapes

Abstract: Abstract. In this paper, we present a new motion planning strategy for shepherding in environments containing obstacles. This instance of the group motion control problem is applicable to a wide variety of real life scenarios, such as animal herding simulation, civil crowd control training, and oil-spill cleanup simulation. However, the problem is challenging in terms of scalability and robustness because it is dynamic, highly underactuated, and involves multi-agent coordination. Our previous work showed that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(7 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…Following their previous research ( [9], [10], [13], [51]), Harrison, Vo and Lien [52] produced a new control method for shepherding a swarm, in which the shepherd models the swarm as an abstract, deformable shape. Using this abstraction, the shepherd continually updates the current swarm shape by calculating a new desired distribution, then moving to steering points behind the swarm (with respect to the goal location) to achieve it.…”
Section: Shepherding Control Methodsmentioning
confidence: 99%
“…Following their previous research ( [9], [10], [13], [51]), Harrison, Vo and Lien [52] produced a new control method for shepherding a swarm, in which the shepherd models the swarm as an abstract, deformable shape. Using this abstraction, the shepherd continually updates the current swarm shape by calculating a new desired distribution, then moving to steering points behind the swarm (with respect to the goal location) to achieve it.…”
Section: Shepherding Control Methodsmentioning
confidence: 99%
“…The design of an adversarial strategy that the UAVs can apply when the AALVs are actively trying to escape is considered to be a counter-strategy to the well-studied herding controllers discussed in refs. [1, 4, 5], where the objective is to guide a group of agents toward a certain area. Some of these controllers are bio-inspired herding mechanisms (e.g., sheepdogs guiding a herd of sheep) [2, 3] that can also be applied to swarming agents on both ends, as seen in ref.…”
Section: Related Workmentioning
confidence: 99%
“…It was later found that shepherd movement based only on the agents' center of mass is effective [3], although cooperation and/or synchronization was not considered. Other non-traditional herding methods involve the abstraction of the flock's geometry as a deformable blob [4], which is useful when the flock has a complex motion or grows considerably in size. In general, shepherding methods and their outcomes thrive in simulation environments but real applications are intended for swarm robotic systems [5].…”
Section: Introductionmentioning
confidence: 99%
“…For instance, Vo et al [10] proposed a behavior-based method which selects intermediate goals on the roadmap of the workspace medial axis. Harrison et al [11] developed a deformable shape model for shepherding control, they modeled the swarm robots as a deformable shape, in their method, the shepherd continually computes the swarm shape and move to the steering points based on the swarm shape. Strömbom et al [12] proposed a heuristic method and described two behaviors: driving and collecting.…”
Section: Related Workmentioning
confidence: 99%